The Influence of Performance Appraisal and Reward on Employee Performance ss Mediated by Employee Job Satisfaction on PT. Expert Jaya Group (Property Company) - Rosdiana, Arfiya; Johanes, Singmin (Journal of Advances in Accounting, Economics, and Management, 2024)
This research aims to analyze the factors that influence employee performance based on performance appraisal, rewards and employee job satisfaction at PT Expert Jaya Group. The population of this research is employees from PT Expert Jaya Group with a sample size of 104 permanent employees. The data analysis method uses Structural Equation Model Partial Least Square (SEM-PLS). The results of the study found that performance appraisal has a significant effect on employee performance, performance appraisal has a significant effect on employee job satisfaction, rewards have no effect on employee performance, rewards have a significant effect on employee job satisfaction, employee job satisfaction has a significant effect on employee performance, employee job satisfaction significantly mediates performance appraisal of employee performance, and employee job satisfaction significantly mediate rewards on employee performance.